Pulmonary Artery Occlusion and Mediastinal Fibrosis in a Patient on Dopamine Agonist Treatment for Hyperprolactinemia - Junjing Su; Ulf Simonsen; Jørn Carlsen; Soren Mellemkjaer (Frontiers Media S.A., 2017)
Unusual forms of pulmonary hypertension include pulmonary hypertension related to mediastinal fibrosis and the use of serotonergic drugs. Here, we describe a patient with diffuse mediastinal fibrosis and pulmonary hypertension while she was on dopamine agonist therapy. A young woman, who was treated with cabergoline and bromocriptine for hyperprolactinemia, presented with progressive dyspnea over several months. Based on the clinical investigation results, in particular, elevated pulmonary arterial pressures and significant perfusion defects on computed tomography (CT) pulmonary angiography and ventilation/perfusion (V/Q) scintigraphy, chronic thromboembolic pulmonary hypertension (CTEPH) was initially considered the most plausible diagnosis. However, during an attempted pulmonary endarterectomy, loose fibrous tissues were observed in the mediastinum and cryosection of the right pulmonary artery showed fibrosis and chronic inflammation. Subsequent investigations revealed that diffuse mediastinal fibrosis with concurrent pulmonary hypertension, and not CTEPH, was the most likely diagnosis and cabergoline and bromocriptine may have triggered the fibrotic changes. Both drugs are ergot-derived dopamine agonists, which are known to cause cardiac valve fibrosis and less frequently, non-cardiac fibrotic changes. The underlying mechanism is attributed to their interactions with serotonin receptors. There is much evidence that serotonin, a potent vasoconstrictor and mitogen, is involved in the pathogenesis of pulmonary hypertension. In conclusion, as CT and V/Q scintigraphy findings can occasionally be deceptive, physicians should be particularly aware of differential diagnoses in patients without obvious history of venous thromboembolism that are suspected of having chronic thromboembolic pulmonary hypertension.